PERANCANGAN STRATEGI E-COMMERCE BERBASIS WEBSITE UNTUK MENINGKATKAN PENJUALAN (STUDI KASUS â€œSONGKETKITOâ€ KAIN KHAS PALEMBANG) - Nugroho B Sukamdani; Wahyu Istuningsih (JURNAL EKONOMI BISNIS DAN KEWIRAUSAHAAN, 2018)
Songket is a special cloth of Palembang which is much in demand by the people both domestic and foreign. â€œSongket kitoâ€ is one of the businesses that produce a unique songket product Palembang. Songket from Palembang gets the title â€œQueen of All Fabricsâ€ because it is one type of quality woven fabric because it is woven with gold and silver threads so that the songket cloth is quite expensive selling price. Marketing that only focuses on southern sumatera area gives the impact of songket weaving less developed. Along with the development of information and communication technology can be utilized to design marketing strategy to increase sales of products through cyberspace or often called E-commerce. One of them by designing a website-based marketing strategy. The results of sales and marketing of products through the website has provided many fnancial advantages as well as the high buyers and breadth of product marketing area and can be stated the application of E-commerce is not familiar with space and time, can be done anytime and anywhere